2021
DOI: 10.1098/rsos.210822
|View full text |Cite
|
Sign up to set email alerts
|

Diverse stem-chondrichthyan oral structures and evidence for an independently acquired acanthodid dentition

Abstract: The teeth of sharks famously form a series of transversely organized files with a conveyor-belt replacement that are borne directly on the jaw cartilages, in contrast to the dermal plate-borne dentition of bony fishes that undergoes site-specific replacement. A major obstacle in understanding how this system evolved is the poorly understood relationships of the earliest chondrichthyans and the profusion of morphologically and terminologically diverse bones, cartilages, splints and whorls that they possess. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…2-4, 6C-F). A large lateral fossa provided an insertion site for the mandibular adductor while a ventrolateral groove would have carried the dermal mandibular splint, which matches the description of Dearden & Giles (2021). The mandibles are separate, but the expanded anterior tip suggests a well-developed symphysis, which may be a character uniting some stem-group chondrichthyans (Dearden & Giles, 2021).…”
Section: Mandibular Archsupporting
confidence: 53%
See 2 more Smart Citations
“…2-4, 6C-F). A large lateral fossa provided an insertion site for the mandibular adductor while a ventrolateral groove would have carried the dermal mandibular splint, which matches the description of Dearden & Giles (2021). The mandibles are separate, but the expanded anterior tip suggests a well-developed symphysis, which may be a character uniting some stem-group chondrichthyans (Dearden & Giles, 2021).…”
Section: Mandibular Archsupporting
confidence: 53%
“…This includes in aspects of the specialised mandibular apparatus: the expanded anterior end of the Meckel's cartilage appears to be present in Halimacanthodes (Burrow et al, 2012;Dearden & Giles, 2021), while a double-faceted palatoquadrate has been reported in Cheiracanthus (Miles, 1973a). Although Acanthodes is often characterised as the last gasp of the doomed acanthodians, it is perhaps better framed as the last member of a 100 million year-old lineage with a success based in an innovative feeding mechanism.…”
Section: Functional Anatomy Of the Jawmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these mineralized fragments, isolated teeth consist of layers of dentine and enameloid which are some of the hardest biological tissues, often resulting in the only remains left of a decayed and fragmented cartilaginous fish. Crownward chondrichthyans furthermore grow, shed and replace their teeth throughout their lifetime which may further complicate this bias [ 99 , 100 ]. Rates of replacement in fossil taxa are mostly unknown and suggested to have been slow [ 101 ] and there is good evidence of tooth retention throughout life in Palaeozoic cladodonts [ 99 ].…”
Section: Discussionmentioning
confidence: 99%